Presenilin-1 Mutations Are a Cause of Primary Lateral Sclerosis-Like Syndrome - Vázquez-Costa, Juan Francisco; Payá-Montes, María; Martínez-Molina, Marina; Jaijo, Teresa; Szymanski, Jazek; Mazón, Miguel; Sopena-Novales, Pablo; , ENoD Consortium; Pérez-Tur, Jordi; Sevilla, Teresa; Morte, Beatriz; Carmona, Rosario; et al. (Frontiers in Molecular Neuroscience, 2021)
Background and Purpose Primary lateral sclerosis (PLS) is a progressive upper motor neuron (UMN) disorder. It is debated whether PLS is part of the amyotrophic lateral sclerosis (ALS) spectrum, or a syndrome encompassing different neurodegenerative diseases. Recently, new diagnostic criteria for PLS have been proposed. We describe four patients of two pedigrees, meeting definite PLS criteria and harboring two different mutations in presenilin 1 (PSEN1). Methods Patients underwent neurological and neuropsychological examination, MRI, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET), amyloid-related biomarkers, and next-generation sequencing (NGS) testing. Results Four patients, aged 25–45 years old, presented with a progressive UMN syndrome meeting clinical criteria of definite PLS. Cognitive symptoms and signs were mild or absent during the first year of the disease but appeared or progressed later in the disease course. Brain MRI showed microbleeds in two siblings, but iron-related hypointensities in the motor cortex were absent. Brain FDG-PET showed variable areas of hypometabolism, including the motor cortex and frontotemporal lobes. Amyloid deposition was confirmed with either cerebrospinal fluid (CSF) or imaging biomarkers. Two heterozygous likely pathogenic mutations in PSEN1 (p.Pro88Leu and p.Leu166Pro) were found in the NGS testing. Conclusion Clinically defined PLS is a syndrome encompassing different neurodegenerative diseases. The NGS testing should be part of the diagnostic workup in patients with PLS, at least in those with red flags, such as early-onset, cognitive impairment, and/or family history of neurodegenerative diseases.